Library and information center management - Stueart, Robert D. (Libraries Unlimited, 1993)
Any textbook that reaches its sixth edition has achieved classic status! Stueart was a longtime professor and dean at Simmons College. Moran has been a professor and dean at the University of North Carolina. Their challenge is to apply the best practices from the management discipline in a meaningful way to the institutions and operations of library and information science (LIS) and at the same time to make this non-LIS field interesting to LIS students. They meet this challenge by examining through a management lens the basic processes and operations of LIS institutions: evolution (of management as a facilitative process), planning, organizing, staffing (human resources), leading, and coordinating. Illustrations, tables, and sources abound.